Recurrent mycotic cerebral aneurysm in a pediatric patient. Case report - Tandazo, Samantha; Nievas, Melisa; Rugilo, Carlos; Requejo, Flavio (Revista Argentina de Neurocirugía, 2026)
Background: cerebral aneurysms in pediatrics represent less than 1% of patients under 15 years of age. "Mycotic" aneurysms occur due to deterioration of the arterial wall, generating a blind "saculation" adjacent to its lumen due to the action of an infectious agent, predominantly bacteria, leading to infective endocarditis.Objectives: to describe the distant presentation of a second mycotic aneurysm in a patient with leukemia and a history of invasive fungal infection due to Aspergillus.Case description: a16-year-old male patient with a history of acute lymphocytic leukemia presented with a right cerebellar abscess, with subsequent bleeding in the surgical bed secondary to a mycotic aneurysm of the posterior cerebral artery. With galactomannan rescue in the blood and a chest CT scan consistent with associated respiratory infection, treatment for invasive Aspergillus infection was initiated.Surgery: endovascular treatment of the aneurysm was performed. Follow-up magnetic resonance imaging (MRI) revealed a fusiform dilation of the anterior communicating artery with involvement of the left A2 segment, associated with irregularity in the right M1 segment. A flow diverter was placed using endovascular therapy plus balloon plasty and coil placement.Conclusion: endovascular treatment, complemented by antimicrobial therapy, requires prolonged follow-up with cerebral MRI to detect recurrence and reduce the risk of fatal bleeding.
Keywords: Aneurysm; Endovascular; Mycotic; Pseudoaneurysm